Measuring women's empowerment in national surveys: Development of the Women’s Empowerment Metric for National Statistical Systems (WEMNS) - Seymour, Greg; Heckert, Jessica; Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Malapit, Hazel J.; Paz, Florencia; Faas, Simone; Myers, Emily; Doss, Cheryl; Sinharoy, Sheela S.; Cheong, Yuk Fai; Yount, Kathryn M.; et al. (International Food Policy Research Institute, 2024)
Monitoring progress toward Sustainable Development Goal (SDG) 5—achieving gender equality and empowering all women and girls—remains challenging unless we incorporate women’s empowerment metrics into nationally representative and multi-topic surveys. To address this data gap, we designed the Women’s Empowerment Metric for National Statistical Systems (WEMNS) as a streamlined empowerment module suitable for the 50x2030 Initiative, a global partnership that aims to build capacity and close the agricultural data gap in 50 countries by 2030, as well as other large multi-topic surveys. WEMNS measures women’s and men’s empowerment and is applicable to urban and rural areas and a variety of livelihood strategies (farming, self-employment, wage labor) across countries in different stages of structural transformation. WEMNS is a counting-based, multidimensional index composed of four domains: intrinsic agency, instrumental agency, collective agency, and agency-enabling resources. Each domain is measured with binary indicators derived from question sets in the WEMNS module. In this paper, we describe the development and testing of WEMNS and its components, including: (1) WEMNS's distinctiveness from other empowerment metrics; (2) the iterative approach used to develop and pilot the WEMNS module in Bangladesh, Guatemala, Malawi, and Nepal, using cognitive interviewing, phone surveys, and face-to-face surveys; (3) analysis of quantitative pilot data; and (4) a summary of the findings from the cognitive interviewing. The paper concludes with a discussion of lessons learned and possibilities for further development of WEMNS and other empowerment metrics.